PENGARUH KOMPETENSI DAN WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI DENGAN VARIABEL INTERVENING KOMITMEN ORGANISASI PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESAKABUPATEN KUTAI TIMUR - Hareni; Tri Gunarti Ningrum; Nurlianti M; Sugeng Wahyudi (Journal Competency of Business, 2025)
This study examines the influence of competence and work life balance on employee performance with organizational commitment as an intervening variable at the Department of Community Empowerment and Village Affairs (DPMD) of East Kutai Regency. An explanatory quantitative approach was applied using a census of 90 employees as respondents. Data collection utilized a structured Likert scale questionnaire, and data analysis applied Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS software with 5,000 bootstrapping resamples. The results reveal that competence has a significant positive effect on both organizational commitment (β = 0.409, p = 0.000) and employee performance (β = 0.365, p = 0.000). Work life balance has a significant positive effect on organizational commitment (β = 0.238, p = 0.003) but does not directly affect employee performance significantly (β = 0.122, p = 0.207). Organizational commitment significantly influences employee performance (β = 0.337, p = 0.000). Organizational commitment partially mediates the effect of competence on employee performance (β indirect = 0.138, p = 0.002), and fully mediates the effect of work life balance on employee performance (β indirect = 0.080, p = 0.014). These findings underscore the critical role of organizational commitment as a psychological bridge between human resource factors and employee performance in local government settings.